Practical application of the progesterone P4 rapid test in cow's milk for early pregnancy detection - Mehmedi, Blerta (Array, 2020)
Pregnancy diagnosis is an essential part of fertility management in cattle. Early detection of pregnancy 21 days after artificial insemination (AI) allows for early recognition and rebreeding of non-pregnant animals with a minimum delay, which benefits the economic interest for farmers. Rapid progesterone P4 tests are widely used in fertility management strategies, yet there is limited data about the efficiency of tests for P4 measurements in cow"s milk. By measuring P4 concentrations in the milk of different breeds: Red Holstein, Black-Holstein, Simmental, and local crossbreeds, this study aimed to assess the practical application and efficiency of an early and rapid pregnancy detection test from cow"s milk. The study was conducted in 2017–2018 and milk samples were taken from animals at day 21 after artificial insemination (AI) to diagnose pregnancy. The test indicated that of the total cows (n=400) included in this study, 69% were pregnant and 31% were not pregnant, as interpreted based on the P4 Rapid (Ridgeway Science UK) test results. Accuracy of the early diagnosis was verified 60 days after AI (without further AI of cows) by rectal palpation. Based on this examination, 263 (66%) cows were diagnosed as pregnant, while 14 (34%) were diagnosed as non-pregnant. The highest accuracy in pregnancy detection was found in the local crossbreeds and the Simmental breed, with 97% correct diagnosis of cows, followed by Red Holstein with 94% and Black Holstein with an accuracy of 90%. This study showed that the use of progesterone P4 rapid tests in milk samples is an effective, fast and accurate method for the early detection of pregnancy in cows, with an accuracy rate of 90 to 97% based on cattle breed.